Utilization of Kalpataru Flower Extract (Hura crepitans Linn) as an Alternative Acid Base Indicator - Bayu Riswanto; Sitti Aminah (Universitas Tadulako, 2020)
Kalpataru flower (Hura crepitans Linn) is an anthocyanin-containing plant. This study aims to utilize extract from the kalpataru flower as an alternative acid base indicator and determine the type of acid-base titration suitable for extracting the kalpataru flower indicator. Kalpataru flowers are macerated with methanol solvent for around 2 hours. Kalpataru flower extract was tested as an indicator in acid-base solution, buffer, and compared with phenolphthalein and methyl orange for acid-base titration, namely: strong acids with strong bases, weak acids with strong bases, and weak bases with strong acids. The results obtained in this study were: indicator extract of brownish yellow kalpataru flowers, in strong red acids, in strong bases of dark green, in weak pink acids, and in weak bases in light green. In the buffer, the indicator extract of the kalpataru flower has a range of pH pH 4-5 (pink-colorless) and pH 9-11 (yellowish green-dark green). The indicator of kalpataru flower extract can be used on strong acid titration with strong bases, weak acids with strong bases and weak bases with strong acids. Kalpataru flower extract can be used as an acid-base indicator.